EFFECT OF CLOVE OIL IN DROPLET COMBUSTION OF CRUDE JATROPHA OIL - Adhes Gamayel, M.N. Mohammed, Salah Al-Zubaidi , Eddy Yusuf (International Journal of Advanced Science and Technology, 2020)
The present study is concerned with the flame shape formation due to micro-explosion phenomena in crude jatropha oil – clove oil blend. In this study, CJO blend with clove oil of 1% to 5% volume percentages to produce five oil blends namely; CJOC1, CJOC2, CJOC3, CJOC4, CJOC5. Single droplet combustion experimental was prepared to know the flame evolution and micro-explosion phenomena. Based on flame evolution, CJOC5 have the shortest ignition time and micro-explosion. It is due to the presence of eugenol and terpene that involved in clove oil, lead to lower ignition delay and rapid combustion. The Differences of evaporation rate between clove oil and CJO made bubble to come out outside the main droplet and lead to formation of spherical flame at all percentage of fuel blends.